The Great financial crisis in finland and Sweden : the dynamics of boom, bust and recovery 1985- 2000 - Jonung, Lars.; Kiander, Jaakko; Vartia, Pentti; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
This paper explores the anatomy of the boom, deep depression and recovery in the Finnish and Swedish economies in the period 1985-2000. These fifteen years are divided into three phases: (1) financial liberalization and the boom and the overheating of 1985-90, (2) the outbreak and spread of the crisis to all sectors of the economy in 1990-92, and (3) the recovery 1993-2000. Each period is analyzed separately.
Economic Papers.